Blood pressure reduction after renal denervation in patients with or without chronic kidney disease - Günes-Altan, Merve; Schmid, Axel; Ott, Christian; Bosch, Agnes; Pietschner, Robert; Schiffer, Mario; Uder, Michael; Schmieder, Roland; Kannenkeril, Dennis (Clinical Kidney Journal, 2024)
Background. Renal denervation (RDN) has emerged as an adjacent option for the treatment of hypertension. This analysis of the Erlanger registry aimed to compare the blood pressure (BP)-lowering effects and safety of RDN in patients with and without chronic kidney disease (CKD). Methods. In this single-center retrospective analysis, 47 patients with and 127 without CKD underwent radiofrequency-, ultrasound- or alcohol-infusion-based RDN. Office and 24-h ambulatory BP and estimated glomerular filtration rate (eGFR) were measured at baseline, and after 6 and 12 months. Results. A total of 174 patients with a mean age of 59.0 ± 10 years were followed up for 12 months. At baseline, mean eGFR was 55.8 ± 21 mL/min/1.73 m2 in patients with CKD and 87.3 ± 13 mL/min/1.73 m2 in patients without CKD. There was no significant eGFR decline in either of the groups during 12 months of follow-up. In patients without CKD, office systolic and diastolic BP were reduced by –15.3 ± 17.5/–7.9 ± 10.8 mmHg 6 months after RDN and by –16.1 ± 18.2/–7.7 ± 9.6 mmHg 12 months after RDN. In patients with CKD, office systolic and diastolic BP were reduced by –10.7 ± 24.0/–5.8 ± 13.2 mmHg 6 months after RDN and by –15.1 ± 24.9/–5.9 ± 12.9 mmHg 12 months after RDN. Accordingly, in patients without CKD, 24-h ambulatory systolic and diastolic BP were reduced by –7.2 ± 15.8/–4.9 ± 8.8 mmHg 6 months after RDN and by –9.0 ± 17.0/–6.2 ± 9.8 mmHg 12 months after RDN. In patients with CKD, 24-h systolic and diastolic BP were reduced by –7.4 ± 12.9/–4.2 ± 9.9 mmHg 6 months after RDN and by –8.0 ± 14.0/–3.6 ± 9.6 mmHg 12 months after RDN. There was no difference in the reduction of office and 24-h ambulatory BP between the two groups at any time point (all P > .2). Similar results have been found for the 6 months data. With exception of rare local adverse events, we did not observe any safety signals. Conclusion. According to our single-center experience, we observed a similar reduction in 24-h, day and night-time ambulatory BP as well as in-office BP in patients with and without CKD at any time point up to 12 months. We conclude that RDN is an effective and safe treatment option for patients with hypertension and CKD.
CRIS-Team Scopus Importer:2024-01-26
Keywords: blood pressure; chronic kidney disease; hypertension; post-hoc analysis; renal denervation

Is GFR decline induced by SGLT2 inhibitor of clinical importance? - Günes-Altan, Merve; Bosch, Agnes; Striepe, Kristina; Bramlage, Peter; Schiffer, Mario; Schmieder, Roland; Kannenkeril, Dennis (Cardiovascular Diabetology, 2024)
Background: Use of sodium-glucose-cotransporter-2 (SGLT2) inhibitors often causes an initial decline in glomerular filtration rate (GFR). This study addresses the question whether the initial decline of renal function with SGLT2 inhibitor treatment is related to vascular changes in the systemic circulation. Methods: We measured GFR (mGFR) and estimated GFR (eGFR) in 65 patients with type 2 diabetes (T2D) at baseline and after 12 weeks of treatment randomized either to a combination of empagliflozin and linagliptin (SGLT2 inhibitor based treatment group) (n = 34) or metformin and insulin (non-SGLT2 inhibitor based treatment group) (n = 31). mGFR was measured using the gold standard clearance technique by constant infusion of inulin. In addition to blood pressure (BP), we measured pulse wave velocity (PWV) under standardized conditions reflecting vascular compliance of large arteries, as PWV is considered to be one of the most reliable vascular parameter of cardiovascular (CV) prognosis. Results: Both mGFR and eGFR decreased significantly after initiating treatment, but no correlation was found between change in mGFR and change in eGFR in either treatment group (SGLT2 inhibitor based treatment group: r=-0.148, p = 0.404; non-SGLT2 inhibitor based treatment group: r = 0.138, p = 0.460). Noticeably, change in mGFR correlated with change in PWV (r = 0.476, p = 0.005) in the SGLT2 inhibitor based treatment group only and remained significant after adjustment for the change in systolic BP and the change in heart rate (r = 0.422, p = 0.018). No such correlation was observed between the change in eGFR and the change in PWV in either treatment group. Conclusions: Our main finding is that after initiating a SGLT2 inhibitor based therapy an exaggerated decline in mGFR was related with improved vascular compliance of large arteries reflecting the pharmacologic effects of SGLT2 inhibitor in the renal and systemic vascular bed. Second, in a single patient with T2D, eGFR may not be an appropriate parameter to assess the true change of renal function after receiving SGLT2 inhibitor based therapy. Trial registration: clinicaltrials.gov (NCT02752113).
CRIS-Team Scopus Importer:2024-06-14
Keywords: GFR decline; PWV; SGLT2 inhibitors

Skin sodium content as a predictor of blood pressure response to renal denervation - Günes-Altan, Merve; Schmid, Axel; Kannenkeril, Dennis; Linz, Peter; Ott, Christian; Bosch, Agnes; Schiffer, Mario; Uder, Michael; Schmieder, Roland (Hypertension Research, 2023)
Patients with treatment resistant hypertension (TRH) are known to have elevated sodium (Na) content in muscle and skin. Renal denervation (RDN) emerged as an adjacent therapeutic option in this group of patients. This analysis aimed at evaluating whether tissue Na content predicts blood pressure (BP) response after RDN in patients with TRH. Radiofrequency-device based RDN was performed in 58 patients with uncontrolled TRH. Office and 24-h ambulatory BP were measured at baseline and after 6 months. To assess tissue Na content Na magnetic resonance imaging (Na-MRI) was performed at baseline prior to RDN. We splitted the study cohort into responders and non-responders based on the median of systolic 24-h ambulatory blood pressure (ABP) reduction after 6 months and evaluated the association between BP response to RDN and tissue Na content in skin and muscle. The study was registered at http://www.clinicaltrials.gov (NCT01687725). Six months after RDN 24-h ABP decreased by −8.6/−4.7 mmHg. BP-Responders were characterized by the following parameters: low tissue sodium content in the skin (p = 0.040), female gender (p = 0.027), intake of aldosterone antagonists (p = 0.032), high baseline 24-h night-time heart rate (p = 0.045) and high LDL cholesterol (p < 0.001). These results remained significant after adjustment for baseline 24-h systolic BP. Similar results were obtained when the median of day-time and night-time ABP reduction after 6 months were used as cut-off criteria for defining BP response to RDN. We conclude that in addition to clinical factors including baseline 24-h ABP Na-MRI may assist to select patients with uncontrolled TRH for RDN treatment. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-11-03
Keywords: Renal denervation; Sodium MRI; Tissue sodium